MONITORING AND ANALYSIS OF ADVERSE DRUG REACTIONS IN A PRIVATE TERTIARY CARE TEACHING HOSPITAL - Roy, Kiran; S, Divya; Nadig, Pratibha; Bhanuprakash, . (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Â  Objectives: To monitor and analyse the suspected adverse drug reactions (ADRs) reported at Vydehi Hospital, Bengaluru. Methods: A prospective observational study was conducted between July 2011 and August 2012. Suspected ADR - Central Drugs Standard Control Organization forms submitted to pharmacovigilance unit were analysed for: (1) Type of reaction, (2) severity, (3) seriousness, (4) causal relationship with the drug using the Naranjo and World Health Organisation (WHO) - UMC causality scale, (5) predictability of ADR and (6) group of suspected drugs associated with ADR. Results: 45 forms out 54 were complete as per the Pharmacovigilance Programme of India, which were analysed. 44 (97.7%) of the reactions were Type B and 1 (2.2%) Type A. 24 (53.3%) of the reactions were mild, 20 (44.4%) were moderate, and 1 (2.2%) severe. 4 (8.8%) reactions were considered serious. As per the Naranjo causality scale, 81.8% were possibly related and 18.2% probably related. Analysis as per WHO-UMC causality scale showed that 16.6% of the reactions were probably or likely related and 83.3% possibly related. The predictability of an ADR was assessed for 30 of the 45 reports where single drug or fixed drug combination were prescribed. 27 (90%) were considered predictable amongst them. The major group of drugs that caused the reactions were antimicrobials. The most common ADRs in our study were cutaneous reactions. 37.7% of ADRs were noted in patients on combination of drugs. Conclusions: Study revealed that the reporting rate was low. Only cutaneous reactions were reported. More awareness needs to be created to address these issues. Keywords: Adverse drug reactions, Pharmacovigilance, WHO-UMC, Naranjo's casuality scale. Â 